Astrogenesis in the murine dentate gyrus is a life-long and dynamic process - Schneider, Julia; Weigel, Johannes; Wittmann, Marie-Theres; Svehla, Pavel; Ehrt, Sebastian; Zheng, Fang; Elmzzahi, Tarek; Karpf, Julian; Paniagua-Herranz, Lucia; Basak, Onur; Ekici, Arif Bülent; Wiesmann da Silva Reis, André; et al. (EMBO Journal, 2022)
Astrocytes are highly abundant in the mammalian brain, and their functions are of vital importance for all aspects of development, adaption, and aging of the central nervous system (CNS). Mounting evidence indicates the important contributions of astrocytes to a wide range of neuropathies. Still, our understanding of astrocyte development significantly lags behind that of other CNS cells. We here combine immunohistochemical approaches with genetic fate-mapping, behavioral paradigms, single-cell transcriptomics, and in vivo two-photon imaging, to comprehensively assess the generation and the proliferation of astrocytes in the dentate gyrus (DG) across the life span of a mouse. Astrogenesis in the DG is initiated by radial glia-like neural stem cells giving rise to locally dividing astrocytes that enlarge the astrocyte compartment in an outside-in-pattern. Also in the adult DG, the vast majority of astrogenesis is mediated through the proliferation of local astrocytes. Interestingly, locally dividing astrocytes were able to adapt their proliferation to environmental and behavioral stimuli revealing an unexpected plasticity. Our study establishes astrocytes as enduring plastic elements in DG circuits, implicating a vital contribution of astrocyte dynamics to hippocampal plasticity.
CRIS-Team WoS Importer:2022-04-29

Dentate gyrus astrocytes exhibit layer-specific molecular, morphological and physiological features - Karpf, Julian; Unichenko, Petr; Chalmers, Nicholas; Beyer, Felix; Wittmann, Marie-Theres; Schneider, Julia; Fidan, Elif; Reis, André; Beckervordersandforth, Jan; Brandner, Sebastian; Liebner, Stefan; Falk, Sven; et al. (Nature Neuroscience, 2022)
Neuronal heterogeneity has been established as a pillar of higher central nervous system function, but glial heterogeneity and its implications for neural circuit function are poorly understood. Here we show that the adult mouse dentate gyrus (DG) of the hippocampus is populated by molecularly distinct astrocyte subtypes that are associated with distinct DG layers. Astrocytes localized to different DG compartments also exhibit subtype-specific morphologies. Physiologically, astrocytes in upper DG layers form large syncytia, while those in lower DG compartments form smaller networks. Astrocyte subtypes differentially express glutamate transporters, which is associated with different amplitudes of glutamate transporter-mediated currents. Key molecular and morphological features of astrocyte diversity in the mice DG are conserved in humans. This adds another layer of complexity to our understanding of brain network composition and function, which will be crucial for further studies on astrocytes in health and disease.
CRIS-Team Scopus Importer:2022-12-09

Distribution of Aldh1L1-CreERT2 Recombination in Astrocytes Versus Neural Stem Cells in the Neurogenic Niches of the Adult Mouse Brain - Beyer, Felix; Lüdje, Wichard; Karpf, Julian; Saher, Gesine; Beckervordersandforth, Ruth (Frontiers in Neuroscience, 2021)
In the adult central nervous system, neural stem cells (NSCs) reside in two discrete niches: the subependymal zone (SEZ) of the lateral ventricle and the subgranular zone (SGZ) of the dentate gyrus (DG). Here, NSCs represent a population of highly specialized astrocytes that are able to proliferate and give rise to neuronal and glial progeny. This process, termed adult neurogenesis, is extrinsically regulated by other niche cells such as non-stem cell astrocytes. Studying these non-stem cell niche astrocytes and their role during adult neuro- and gliogenesis has been hampered by the lack of genetic tools to discriminate between transcriptionally similar NSCs and niche astrocytes. Recently, Aldh1L1 has been shown to be a pan-astrocyte marker and that its promoter can be used to specifically target astrocytes using the Cre-loxP system. In this study we explored whether the recently described Aldh1L1-CreERT2 mouse line (Winchenbach et al., 2016) can serve to specifically target niche astrocytes without inducing recombination in NSCs in adult neurogenic niches. Using short- and long-term tamoxifen protocols we revealed high recombination efficiency and specificity in non-stem cell astrocytes and little to no recombination in NSCs of the adult DG. However, in the SEZ we observed recombination in ependymal cells, astrocytes, and NSCs, the latter giving rise to neuronal progeny of the rostral migratory stream and olfactory bulb. Thus, we recommend the here described Aldh1L1-CreERT2 mouse line for predominantly studying the functions of non-stem cell astrocytes in the DG under physiological and pathological conditions.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Aldh1L1; Aldh1L1-CreER; astrocytes; dentate gyrus; neural stem cells; neurogenic niche; subependymal zone